2020
DOI: 10.7759/cureus.9445
|View full text |Cite
|
Sign up to set email alerts
|

Neutropenic Enterocolitis and Rapid Spontaneous Resolution of Portal Venous Gas: A Non-Respiratory Manifestation of COVID-19

Abstract: The COVID-19 pandemic is affecting millions across the globe. The population of immunosuppressed individuals are at greatest risk of morbidity and mortality. Data on COVID-19 induced illness in the immunocompromised host are sparse. We aim to highlight the possibility of atypical and non-respiratory presentations of COVID-19 (severe acute respiratory syndrome coronavirus 2, SARS-CoV-2) in immunosuppressed individuals as our case reveals a rare COVID-19 associated GI presentation of neutropenic enterocolitis wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…Abdominal CT is beneficial in diagnosing typhlitis and can demonstrate circumferential bowel wall thickening and edema in the relevant bowel segments (usually in the cecum and ascending colon) and peri-intestinal fat-stranding. Moreover, bowel wall thickening is the most sensitive imaging finding and is sufficient to suggest typhlitis diagnosis in the correct clinical and laboratory findings [ 1 , 2 , 7 ]. Rehman et al [ 7 ] recently reported an immunosuppressed patient with COVID-19 and typhlitis, whose general condition deteriorates rapidly.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Abdominal CT is beneficial in diagnosing typhlitis and can demonstrate circumferential bowel wall thickening and edema in the relevant bowel segments (usually in the cecum and ascending colon) and peri-intestinal fat-stranding. Moreover, bowel wall thickening is the most sensitive imaging finding and is sufficient to suggest typhlitis diagnosis in the correct clinical and laboratory findings [ 1 , 2 , 7 ]. Rehman et al [ 7 ] recently reported an immunosuppressed patient with COVID-19 and typhlitis, whose general condition deteriorates rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, bowel wall thickening is the most sensitive imaging finding and is sufficient to suggest typhlitis diagnosis in the correct clinical and laboratory findings [ 1 , 2 , 7 ]. Rehman et al [ 7 ] recently reported an immunosuppressed patient with COVID-19 and typhlitis, whose general condition deteriorates rapidly. Similarly, the clinical condition deteriorated rapidly in the present case, and the patient was died.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dentro de los reportes de tiflitis asociados a COVID-19, existe un caso de desarrollo de esta entidad con un conteo de neutrófilos mayor a 1000 / µl, que es otra característica única de la enterocolitis inducida por COVID-19 (18) . Este paciente no presentó neutropenia al igual que el de nuestro caso.…”
Section: Discussionunclassified